Humans as prey: coping with large carnivore attacks using a predator-prey interaction perspective - Penteriani, Vincenzo; Bombieri, Giulia; Fedriani, José M.; López-Bao, José V.; Garrote, Pedro J.; Russo, Luca Francesco; Delgado, María del Mar (Berryman Institute, 2017)
The number of attacks on humans by large carnivores in North America is increasing. A better understanding of the factors triggering such attacks is critical to mitigating the risk of future encounters in landscapes where humans and large carnivores coexist. Since 1955, of the 632 attacks on humans by large carnivores, 106 (17%) involved predation. We draw on concepts and empirical evidence from the Predator-Prey Interaction Theory to provide insights into how to reduce predatory attacks and, thus, improve human-large carnivore coexistence. Because large carnivore-caused mortality risks for humans are comparable to those shown by other mammal species in response to predation risk, framing predatory attacks under a theory underpinning predator-prey interactions may represent a powerful tool for minimizing large carnivore attacks. Most large carnivores have marked crepuscular and nocturnal activity; by minimizing outdoor activities in high-risk areas from sunset to sunrise, humans could reduce the number of predatory attacks. The most eff ective way in which prey avoid predation, but still utilize risky areas, is by adopting temporal changes in activity patterns. The human age groups most often targeted by large carnivores are essentially the same as when predators in general search for prey, namely the youngest individuals. Thus, increased parental vigilance and education for children may be a key factor to reduce predatory attacks. Lastly, because group size can aff ect predator-prey encounter rates and outcomes in diff erent ways, large groups of people can decrease predation rates. Many humans may no longer consider predation by large carnivores to be a logical or plausible consequence of our predator-naïve behavior because humans now only occasionally represent prey for such species. However, the solution to the confl icts represented by large carnivore attacks on humans requires the implementation of correct strategies to face these rare events.